2009
DOI: 10.3113/fai.2009.0579
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Controlled Trial of STAR Total Ankle Replacement versus Ankle Fusion: Initial Results

Abstract: By 24 months, ankles treated with STAR ankle replacement (in both the Pivotal and Continued Access Groups) had better function and equivalent pain relief as ankles treated with fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
251
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(265 citation statements)
references
References 55 publications
6
251
2
6
Order By: Relevance
“…The cohort age and demographics reflect the mean age and demographics among participants in the largest TAA and ankle fusion studies [20,28]. The TAA study had approximately 50% females and 50% males [20]. The clinical pathway modeled began with patients undergoing a TAA or ankle fusion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cohort age and demographics reflect the mean age and demographics among participants in the largest TAA and ankle fusion studies [20,28]. The TAA study had approximately 50% females and 50% males [20]. The clinical pathway modeled began with patients undergoing a TAA or ankle fusion.…”
Section: Methodsmentioning
confidence: 99%
“…Three different fixedbearing implants and one newer mobile-bearing implant are approved for use in the United States. Some evidence suggests greater longevity in STAR mobile-bearing prostheses over standard fixed-bearing designs [16,20,28]. Furthermore, the study used for the reference case has the largest reported series of TAAs (200 patients), with some of the longest followup data published (range, 5-13 years), and greater than 80% survivorship [28].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One report suggests patients have pain relief and high satisfaction after surgery [4]. Saltzman et al [33] recently published initial findings from a prospective controlled trial of the Scandinavian Total Ankle Replacement System 1 (STAR) TAA versus ankle fusion and reported TAA led to better function and similar pain relief compared with ankles that were fused. One study reported five TAAs in four patients with HH [6] and showed all four patients had good relief of symptoms after surgery.…”
Section: Introductionmentioning
confidence: 99%